Enterprise Economic Security in Time of Digital Transformation - A. A. Dokukina; V. V. Pimenov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with specific features of today’s organization in time of information economy and grounds the necessity to develop a management model based on principles of enterprise architecture and its interaction with the ecosystem on the background of digital transformation. It studies preconditions of shaping new approaches to enterprise management and their significance for developing the effective business-model in time of digital transformation; substantiates the efficiency of using syndinics as the concept basis for practical solutions aimed at system threat minimization. The problem of field covering strategy, tools and methods of providing economic security of enterprises in time of digital transformation was identified. The article focuses on enterprise economic security, principle foundations of its ensuring and requirements to methodological support of the development.  The academic field demonstrating problems of attaining economic security and approaches to its appraisal as enterprise strategy was also shown. The key conclusion is connected with the outlook of developing the enterprise business-model, which includes tools for assessing the efficiency of the system of organization economic security.  A final deduction was made about the potential of growth in competitive advantages in circumstances of turbulence with simultaneous retaining of sustainability against threats.